The Effect of Giving Moringa Honey on Stress and Cortisol Levels in Pregnant Women in Maros Regency (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of giving Moringa Honey on Stress and Cortisol Levels in pregnantwomen.This study used a Randomized Controlled Trial With Pre and Post Double Blind, where the parties involved in thestudy such as researchers and respondents did not know the difference between MH (Moringa Honey) and RH (RegularHoney) given to respondents. The research was carried out in the working area of the Turikale Health Center and Lau HealthCenter, Maros Regency, with stress and cortisol levels checking at the Turikale Health Center from February to April 2020.This study was carried out for two months (8 weeks). The sampling technique used was purposive sampling. The sample is 40pregnant women. 20 samples were given MH intervention (Moringa Honey) and 20 samples were given 15 ml/day RH. Inaddition, pregnant women are given blood-enhancing tablets (Fe) which are consumed by the mother before going to bed. Thisstudy was conducted for 8 weeks, saliva samples were taken to determine cortisol levels. Saliva samples were examined usingthe Enzyme-linked immunorbent assay (ELISA) technique and then statistically analyzed using SPSS version 25. Most of therespondents aged between 20-25 years (22.5%), had more than 1 children (45.0%), earned around 1-3 million (42.5%). Theresults showed a decrease in stress in the MH group from 22.35 ± 5.21 to 18.80 ± 1.93 and the RH group from 19.35 ± 3.42 to21.40 ± 2.79. The large difference in the changes in the two groups was seen to be significant with the value (p=0.001 vsp=0.022). There was a decrease in cortisol levels in the MH group from 1.86 ± 1.14 to 0.67 ± 0.63 and in the RH group from1.20 ± 0.95 to 1.77 ± 1.02, the difference was significantly seen in the cortisol levels of the two groups with value (p=0.001 vsp=0.093).As a result, it can be inferred that giving MH (Moringa Honey) to pregnant women has a greater impact on loweringstress and cortisol levels.